Electrochemical nitrogen fixation in metal-N2 batteries: A paradigm for simultaneous NH3 synthesis and energy generation - Islam, Jahidul; Shareef, Mahmud; Zabed, Hossain M.; Qi, Xianghui; Chowdhury, Faisal Islam; Das, Jagotamoy; Uddin, Jamal; Kaneti, Yusuf Valentino; Khandaker, Mayeen Uddin *; Ullah, Md. Habib; Masud, Mostafa Kamal (Elsevier, 2023)
Electrochemical N2 reduction reaction (NRR) has emerged as the most effective alternative to the conventional Haber-Bosch process for N2 fixation. Although NRR is only used in the synthesis of NH3, researchers have recently exploited it in Metal-N2 batteries (hereafter, M-N2 batteries) to kill two birds with one stone by fixing N2 and generating electricity at the same time. There are three types of electrochemical energy storage approaches, namely rechargeable with irreversible electrochemical reaction (under aqueous or non-aqueous conditions), non-rechargeable with irreversible electrochemical reaction (under aqueous conditions), and rechargeable with reversible electrochemical reaction (under non-aqueous conditions). However, the hydrogen evolution reaction (HER) in an aqueous medium takes precedence over the NRR, resulting in a poor Faradic efficiency (FE) for the NRR selectivity. This obvious but unwanted HER causes the low conversion efficiency in aqueous M-N2 batteries. Furthermore, the instability of cathode electrocatalysts causes a significant drop in the overall performance of MN2 batteries. Despite these flaws, M-N2 batteries represent the first step toward simultaneous N2 fixation and energy storage. Herein, we comprehensively review the NRR mechanism, electrochemistry, and performances of M-N2 batteries. With an emphasis on the strategies to design highly efficient cathode catalysts and electrolytes for future M-N2 batteries, we also chronicle the strategies to suppress the undesired HER in M-N2 batteries. Furthermore, based on the photoelectrochemical NRR and solar-powered metal-gas batteries, a future outlook on photo-assisted M-N2 batteries is also provided.